Effective seeding strategy using flat type poly (vinyl alcohol) cryogel for anammox enrichment. (August 2018) - Choi, Minkyu; Cho, Kyungjin; Lee, Seockheon; Chung, Yun-Chul; Park, Joonhong; Bae, Hyokwan
Abstract: In this study, anammox enrichment reactors were operated using flat type poly (vinyl alcohol) cryogel (cryoPVAG) with precultured anammox bacteria (PAB) and activated sludge (AS) from an anoxic tack of the A2O process to evaluate the effect of different seeding sources on anammox enrichment. In addition, cryoPVAGs with different thicknesses (1, 2, and 3 mm) were used to investigate the effects of the thickness on anammox enrichment. The regression analysis with a modified Gompertz model showed that the start-up period of the anammox enrichment using PAB inoculum was approximately 14 days earlier than that of AS inoculum at a nitrogen loading rate of approximately 1 kg-N m −3 day −1 . Substrate diffusion was limited in 3-mm cryoPVAG with respect to trend in nitrogen removal rate. Quantitative PCR analysis indicated that in the initial phase, the 16S rRNA gene copy numbers of anammox microorganism in cryoPVAG were significantly different according to the seeding source, but finally converged to a similar level after anammox enrichment. The anammox reaction was initially promoted by cryoPVAG. Next, anammox biomass detached from cryoPVAG and enriched in the bulk phase to maximize NRR. Illumina MiSeq sequencing revealed that Candidatus Brocadia sinica led to the active anammox reaction, and its relative abundance decreased with increasing gel thickness. Graphical abstract: Image 1 Highlights: Flat type cyroPVAG was utilized for anammox enrichment. Four anammox reactors with different inocula and thicknesses were used. The start-up period of anammox reactors was evaluated by a modified Gompertz model. Substrate diffusion limitation of cryoPVAG was verified at different gel thicknesses. Candidatus Brocadia sinica was the predominant species after anammox enrichment.